2018
DOI: 10.2495/st180011
|View full text |Cite
|
Sign up to set email alerts
|

Rural Tourism: Crossroads Between Nature, Socio-Ecological Decoupling and Urban Sprawl

Abstract: The development of cultural tourism has turned traditional rural landscapes, characterized by their great natural and cultural values, into focus of tourism attraction, causing important changes in the socioeconomic structure of the regions containing them. The enhancement of this tourism highlights the need to design and implement a sustainable management that guarantees the maintenance and conservation of the landscape and the economic development of local populations. This study, localised in the Lozoya Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The respondents had to indicate which aspects of the landscape of those collected in the questionnaire (corresponding to the 16 RES selected; see Table 1) were most attractive to them, by marking the items that most closely matched their preferences. The structure and orientation of the questionnaires had been validated in previous works, with satisfactory results [22,39,[47][48][49].…”
Section: Step 2 Analysis Of Outdoor Recreation Demandmentioning
confidence: 98%
“…The respondents had to indicate which aspects of the landscape of those collected in the questionnaire (corresponding to the 16 RES selected; see Table 1) were most attractive to them, by marking the items that most closely matched their preferences. The structure and orientation of the questionnaires had been validated in previous works, with satisfactory results [22,39,[47][48][49].…”
Section: Step 2 Analysis Of Outdoor Recreation Demandmentioning
confidence: 98%
“…and includes 30 municipalities. The Lozoya Valley is a heterogeneous landscape with forest, settlements, water bodies such as reservoirs and a mosaic of traditional land uses containing pastures, meadows, hedgerows, ash groves and riparian forests, all of which are well preserved in most cases [26]. Over the centuries, the valley has come under different land uses and rural activities which have shaped the landscape and their traditional way of living along the centuries that have resulted in a region of great socio-ecological value.…”
Section: Research Areamentioning
confidence: 99%
“…However, recent studies have shown that increasing tourism and conflicting management legislation caused a rurality loss and an urban sprawl throughout the territory, transforming the ancient agropastoral landscape into a wilderness [28]. The comparison of surveys conducted with visitors in 2007 and 2017 shows that these changes have had an impact on their way of understanding the landscape of the Lozoya Valley: from valuing the cultural components more, to now valuing the "naturalistic" ones more [26]. Landscape to UNESCO by the Spanish National Plan of Cultural Landscape [27].…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations